Molecular and serological detection of Trypanosoma cruzi in dogs (Canis lupus familiaris) suggests potential transmission risk in areas of recent acute Chagas disease outbreaks in Colombia. (2017)
Chagas disease is a zoonotic infection widely distributed in tropical and subtropical regions of America, including more than 50% of the Colombian territory. In the last years, an increase of outbreaks of acute Chagas disease has been observed.